IMPLIKASI PERUBAHAN KEBIJAKAN PEMBATASAN KUOTA PENJUALAN DARI KAWASAN BERIKAT KE PASAR DALAM NEGERI TERHADAP STRATEGI PROGRAM RESTRUKTURISASI BISNIS (KASUS DI PT. SEAMLESS PIPE INDONESIA JAVA) - , Abdul Mujib ([Yogyakarta] : Universitas Gadjah Mada, 2013)
In the era of globalization of today's world trade, competition for markets for industrial products instead of oil and gas has become more intense. Thus it required the efforts of both the entrepreneur or from the government to work together to improve the competitiveness of products made by companies in the country, of which the government provides facilities through development in customs bonded area. On 6 September 2011, Agus D.W. Martowardojo as Minister of Finance of the Republic of Indonesia issued Regulation of the Minister of Finance of the Republic of Indonesia Number of 147/PMK.04/2011 about Bonded area as a revision of the regulations previously bonded. One of the provisions of the revised limit is related to the expenditure of products bonded to other Indonesian customs areas (nonbonded). This study aims to analyze how the impact of regulatory changes on the bonded area of sales quota restrictions bonded to the domestic market, including providing alternative solutions in order to obtain SPIJ for bonded area.